Accuracy of Fractional Flow Reserve Derived From Coronary Angiography - Fearon, William F; Achenbach, Stephan; Engstrom, Thomas; Assali, Abid; Shlofmitz, Richard; Jeremias, Allen; Fournier, Stephane; Kirtane, Ajay J; Kornowski, Ran; Greenberg, Gabriel; Jubeh, Rami; Kolansky, Daniel M; et al. (Circulation (New York, N.Y.), 2019)
Measuring fractional flow reserve (FFR) with a pressure wire remains underutilized because of the invasiveness of guide wire placement or the need for a hyperemic stimulus. FFR derived from routine coronary angiography (FFR ) eliminates both of these requirements and displays FFR values of the entire coronary tree. The FFR Accuracy versus Standard FFR (FAST-FFR) study is a prospective, multicenter, international trial with the primary goal of determining the accuracy of FFR . Coronary angiography was performed in a routine fashion in patients with suspected coronary artery disease. FFR was measured in vessels with coronary lesions of varying severity using a coronary pressure wire and hyperemic stimulus. Based on angiograms of the respective arteries acquired in ≥2 different projections, on-site operators blinded to FFR then calculated FFR using proprietary software. Coprimary end points were the sensitivity and specificity of the dichotomously scored FFR for predicting pressure wire-derived FFR using a cutoff value of 0.80. The study was powered to meet prespecified performance goals for sensitivity and specificity. Ten centers in the United States, Europe, and Israel enrolled a total of 301 subjects and 319 vessels meeting inclusion/exclusion criteria which were included in the final analysis. The mean FFR was 0.81 and 43% of vessels had an FFR≤0.80. The per-vessel sensitivity and specificity were 94% (95% CI, 88% to 97%) and 91% (86% to 95%), respectively, both of which exceeded the prespecified performance goals. The diagnostic accuracy of FFR was 92% overall and remained high when only considering FFR values between 0.75 to 0.85 (87%). FFR values correlated well with FFR measurements ( r=0.80, P<0.001) and the Bland-Altman 95% confidence limits were between -0.14 and 0.12. The device success rate for FFR was 99%. FFR measured from the coronary angiogram alone has a high sensitivity, specificity, and accuracy compared with pressure wire-derived FFR. FFR has the promise to substantially increase physiological coronary lesion assessment in the catheterization laboratory, thereby potentially leading to improved patient outcomes. URL: https://www.clinicaltrials.gov . Unique Identifier: NCT03226262.